Technology use, emotional connection and their relationship: A literature review - Ismail, N.F. (Little Lion Scientific, 2018)
Demand for technology use upsurge as we often rely on technology in completing countless tasks daily. Nowadays, the emerging technologies impact our way of livings in different ways regardless of age. If technology is properly used, it can make betterment to oneâs life, but if it is excessively used, it causes severity to human beings. Impact arises from the excessive use of technology could be hindered if we could be informed about the severity of technology use. The aim of this research is to develop constructs for a scale measuring technology severity among children regarding emotional connection. For this study, emotional connection is defined as a bond or tie to the technology in the form of attachment, engagement or addiction towards mobile devices. The objective of this article is to understand technology use and emotional connection from reviewing literature. Findings from the literature reviewed suggested that there are intersections of characteristics between technology use and emotional connection. Â© 2005 â ongoing JATIT & LLS.